Obliterative le fort’s colpocleisis for acute kidney injury caused by pelvic organ prolapse in elderly woman - E., Rohini; B., Hiremath P.; Sanyal, Urmi; R., Indu N.; Ghosh, Shilpa; Hiremath, Reshma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Pelvic organ prolapse (POP) is the descent of pelvic organs through the vagina, which sometimes causes hydronephrosis. Here authors report a case of an eighty five year old woman with a fourth degree uterine prolapse with obstructive uropathy. She was treated with a conservative surgery Le Fort’s colpocleisis. Following which the patient’s renal functions and symptoms improved. Hence authors conclude that colpocleisis can be considered as the option for elderly women who have completed the family with no desire to preserve the sexual function especially in women with co morbities where pelvic reconstructive surgeries pose a challenge.